Conexões entre o comportamento dos adultos presentes nas aulas de música e o desenvolvimento musical dos bebês nos dois primeiros anos de vida - Dalila Mayara Caetano Werneck Silva (2018)
The objective of this research was to investigate the possible connections between the behavior of adults during music lessons for babies and the musical development of these children. The main framework were Jean Piaget’s ideas about children’s cognitive development; Edwin Gordon, François Delalande, Parizzi, Stifft and Beyer's theories about the child's musical development in the early years of life; and the concepts of "communicative musicality" (MALLOCH, 1999/2000) and "intuitive parenting" (PAPOUSEK, M., 1996), related to baby’s musical development. Three groups of babies were selected and received twelve music lessons in two different contexts: two groups in a specialized music school, with the participation of the parents in the classes, and a regular school group, in which the classes were accompanied by the regular teacher and by an assistant. The classes were filmed and the behavior of the adults present in the classes and the musical development of the babies were verified by a group of independent jurors, composed by experienced musical educators. The jurors' comments were then submitted to a Content Analysis from which emerged patterns that outlined categories that characterized adults’ behavior and the musical development of the participating infants. These categories served as the basis for the correlations that were established between the adults’ behavior in music lessons and the infants’ musical development. The results point to a close relationship between the adults’ behavior and the musical development of infants, so that this development is enhanced by the involvement and expressiveness of the adults present in the classes.